Association between the age-adjusted Charlson Comorbidity Index and complications after kidney transplantation: a retrospective observational cohort study - Qin Huang; Tongsen Luo; Jirong Yang; Yaxin Lu; Shaoli Zhou; Ziqing Hei; Chaojin Chen (BMC Nephrology)
Abstract Background Complications following kidney transplantation elevate the risks of readmission and mortality. The aim of this study was to assess the association between the age-adjusted Charlson Comorbidity Index (ACCI) and postoperative complications among kidney transplant (KT) recipients. Methods Between January 2015 and March 2021, a study involving 886 kidney transplant recipients at the Third Affiliated Hospital of Sun Yat-sen University was conducted. Postoperative complications were defined by the Clavien-Dindo Classification of Surgical Complications. Target Maximum Likelihood Estimation (TMLE) was employed to assess the association between ACCI and postoperative complications. The odds ratio (OR) was computed to determine the relationship between ACCI and postoperative complications. Subsequent interaction and stratified analyses were performed to assess the robustness of the findings. Results Out of 859 KT participants ultimately included in the study, 30.7% were documented to have encountered postoperative complications. Participants with an ACCI value exceeding 3 exhibited a notably increased risk of postoperative complications following multivariable adjustment [aOR = 1.64, 95% CI [1.21,2.21], p = 0.001]. Congestive heart failure (OR = 16.18, 95% CI [1.98–132.17], p < 0.001), peripheral vascular disease (OR = 2.32, 95% CI [1.48–3.78], p < 0.001), and chronic obstructive pulmonary disease (OR = 6.05, 95% CI [2.95–12.39], p < 0.001) emerged as the top three preoperative comorbidities significantly linked to postoperative complications in ACCI. Conclusion An ACCI value exceeding 3 preoperatively constituted a risk factor for postoperative complications among KT patients.